Reinventing giants : - Fischer, Bill (Jossey-Bass, 2013)
This book offers a compelling profile of the most ambitious of these emerging Chinese competitors, the Haier Corporation (the world's largest manufacturer of home appliances), and shares insights on how one organization has repeatedly reinvented its business model and corporate culture in an effort to sustain its success. Reinventing Giants provides an exclusive look within the Haier Corporation and shows how managerial accountability and responsibility have been repositioned at every level of the organization, with the core value of market-centricity, while aligning strategy on each level of management. It includes actual work reports that show this process in detail from the ground up.